2020
DOI: 10.1051/e3sconf/202020207003
|View full text |Cite
|
Sign up to set email alerts
|

Pirates and the Environment: Bajo Tribe Study in Marine Conservation

Abstract: Pirate is considered as one of the oldest professions in the world. The existence of pirates in the archipelago was first recorded in the 5th century AD. In the period of 15th to the 16th century, pirate activities increased due to political and economic changes in the archipelago. One of them was the arrival of European traders which made most people in the archipelago encouraged to do piracy, including those done by Bajo tribe. The tribe which is from Sulawesi was a respected pirate at that time who had a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Small fishermen are generally always victims of human activities on land [35]. The Bajo community has always been famous as a sea community who is very concerned with the conservation of marine resources [36,37]. However, conservation actions which is taken by Bajo people to improve the environment are greatly influenced by the dynamic local socio-political context and individuals who mediate the idea of conservation [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Small fishermen are generally always victims of human activities on land [35]. The Bajo community has always been famous as a sea community who is very concerned with the conservation of marine resources [36,37]. However, conservation actions which is taken by Bajo people to improve the environment are greatly influenced by the dynamic local socio-political context and individuals who mediate the idea of conservation [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research on the Bajaus has revealed several unique characteristics that distinguish them from other customary groups in Indonesia. The Bajaus are very skillful in breath-hold diving (Abrahamsson & Schagatay, 2014), deep knowledge of their marine and coastal environment (Clifton & Majors, 2012;Pauwelussen & Verschoor, 2017;Tomoya & Dedi, 1996;Warsito et al, 2020), and land area (Majid Cooke & Johari, 2019), use of traditional weather forecasting and fishing calendar (Nakano, 2020), unique cosmology (Santamaria, 2019), customary laws (Muslim et al, 2020;Nolde, 2009), and other adaptive management practices Lynch & Turner, 2021).…”
Section: Sea Nomads In Indonesiamentioning
confidence: 99%